Emerging Insights into the Roles of the Rhizome–Culm System in Bamboo Shoot Development through Analysis of Non-Structural Carbohydrate Changes - Tianyi Hu; Linghui Kong; Sisi Hu; Meng Deng; Guangyao Yang; Qiang Wei; Fen Yu (Plants, 2023)
Non-structural carbohydrates (NSCs) required for bamboo shoot development, the critical stage that determines the yield of a bamboo stand, originate from the parent bamboo with the complex underground system. However, the metabolic mechanism of NSCs in the rhizome–culm system during bamboo shoot development remains unclear. In this study, we focused on the changes of NSCs in the rhizome–culm system and used anatomical, physiological, and biochemical methods to investigate the metabolism of NSCs in bamboo shoots of Phyllostachys edulis and the role of NSCs supply in the parent bamboo at different ages. The results showed that NSCs were accumulated and consumed from the bottom to the top in a bamboo shoot, which was consistent with the developmental pattern. The starch granules were stored in advance. The bamboo sheath stored starch from the dormant stage of shoot buds. The functions of culms and rhizomes showed age-dependent differences. Adult culms showed the highest capacity to provide NSCs, with more stored NSCs and higher β-amylase activity. Conversely, young culms seemed to prefer their growth, while old culms tended to store starch. Accordingly, adult rhizomes preferred sugar transport due to the lowest starch storage, lower ADP-glucose pyrophosphorylase (AGPase) activity, and higher β-amylase activity, while young and old rhizomes tended to prefer starch storage. These results provide a basis for further understanding of nutrient metabolism in bamboo stands.